Effects of Coconut Water on Retina in Diabetic Rats. (28th January 2020) - Zhang, Xiaohua; Peng, Li; Dai, Yanan; Sheng, Xia; Chen, Shaomei; Xie, Qing
Abstract : Coconut water (CW) is a natural aseptic nutritious beverage, containing several biologically active compounds. This study aimed to determine the antiretinopathy effects of CW on diabetic Sprague Dawley (SD) rats using streptozotocin (STZ) and explore its potential mechanism. After allowing the rats to acclimatize for 7 days, 48 healthy adult male SD rats were selected and randomly divided into 4 groups, involving control (Ctrl), diabetic rats (DM), diabetic rats treated with CW (DM-CW), and diabetic rats treated with glibenclamide (DM-Gli). The diabetic models were established by an intraperitoneal injection of STZ (60 mg/kg). The Ctrl group was injected with an equal volume of sodium citrate solution. The experiment was totally conducted during 20 weeks, and then, all rats were sacrificed. The serum levels of superoxide dismutase (SOD), malondialdehyde (MDA), and glutathione peroxidase (GSH-Px) were measured; additionally, the activities of interleukin-6 (IL-6) and intercellular adhesion molecule-1 (ICAM-1) in the retina were investigated using biochemical assays. Hematoxylin and eosin (H&E) staining was performed to observe pathological changes of retinal tissues. In presence of treatment with CW, serum level of MDA was decreased, while serum levels of SOD and GSH-Px were increased; besides, the activities of IL-6 and ICAM-1 in the retina were reduced compared with the DM group. The antiretinopathy feature of CW was confirmed by the increased number of neurons in the ganglion cell layer (GCL), total retina thickness (TRT), and thickness of the retinal nuclear layer (RNL) in diabetic rats. CW can be protective against diabetic retinopathy (DR), and its effects are comparable to Gli. The possible underlying mechanism may be partly explained by decreasing oxidative stress and anti-inflammatory activities in the retina. However, further research should be conducted to reveal the exact mechanism.